2011
DOI: 10.1149/2.050201jes
|View full text |Cite
|
Sign up to set email alerts
|

Green-Emitting Ca6Sr4(Si2O7)3Cl2: Eu2+Phosphors for White Light-Emitting Diodes

Abstract: A series of new green-emitting Ca6Sr4-xEux(Si2O7)3Cl2 phosphors were synthesized using the high-temperature solid-state reaction. Thermogravimetry-differential thermal analysis (TG-DTA) and X-ray diffraction (XRD) were used in order to determine the crystallization process and crystal structure of the obtained product. Complete optical studies including the diffuse reflection, photoluminescence excitation and emission measurements were performed. Crystallographic site-occupations of Eu2+ ions in the Ca6Sr4(Si2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Thus, the fundamental absorption edge (bandgap energy) of the NaCaBO 3 host was calculated to be approximately 4.48 eV by extrapolation, essentially due to the transition between the valence band and the conduction band in this host. 24 Obvious differences appear in the spectral profiles of Ce 3+ -doped and Ce 3+ /Mn 2+ -codoped samples compared to that of the NaCaBO 3 host. As the Ce 3+ ions are singly introduced into the NaCaBO 3 host, four absorption bands with maxima at 212, 252, 290, and 360 nm appears in the wavelength range of 200 to 450 nm, which is attributable to the transition from 4f 1 5d 0 to 4f 0 5d 1 of the Ce 3+ ions.…”
Section: Photoluminescence Propertiesmentioning
confidence: 98%
“…Thus, the fundamental absorption edge (bandgap energy) of the NaCaBO 3 host was calculated to be approximately 4.48 eV by extrapolation, essentially due to the transition between the valence band and the conduction band in this host. 24 Obvious differences appear in the spectral profiles of Ce 3+ -doped and Ce 3+ /Mn 2+ -codoped samples compared to that of the NaCaBO 3 host. As the Ce 3+ ions are singly introduced into the NaCaBO 3 host, four absorption bands with maxima at 212, 252, 290, and 360 nm appears in the wavelength range of 200 to 450 nm, which is attributable to the transition from 4f 1 5d 0 to 4f 0 5d 1 of the Ce 3+ ions.…”
Section: Photoluminescence Propertiesmentioning
confidence: 98%
“…They published almost the same results in another paper as well. [ 106 ] Li et al. [ 107 ] confirmed these observations.…”
Section: Alkaline Earth Chlorosilicatesmentioning
confidence: 72%
“…They published almost the same results in another paper as well. [106] Li et al [107] confirmed these observations. They deconvoluted the broad emission band into two Gaussian peaks centered at 508 and 560 nm.…”
Section: Ca 6 Sr 4 (Si 2 O 7 ) 3 CLmentioning
confidence: 78%
“…The wide range of absorption suggests that the phosphor can be effectively excited by n-UV LED chips (350-420 nm). Upon excitation at 277 nm, the PL spectrum of Sr 4.985 Cl 0.75 F 0.25 (PO 4 ) 3 : 0.015Eu 2+ exhibits broad blue emission band extending from 420 to 520 nm with the peak at 445 nm, which is attributed to the electric-dipole allowed 4f-5d transition of Eu 2+ ions [21]. At the excitation of 341 nm, the PL spectrum of the phosphor presents no significant changes except for the emission intensity.…”
Section: Photoluminescence Properties Of Sr 5 CL 075 F 025 (Po 4 ) mentioning
confidence: 99%